Own It. Love It. Make It Work. How to Make Any Job Your Dream Job. Workbook - Tate, Carson (McGraw-Hill, 2020)
A step-by-step workbook to turn any job into your dream job In Own It. Love It. Make It Work ., renowned productivity consultant Carson Tate revealed why many of us are not engaged in our jobs-and offered a new strategy to take ownership of our careers, lives, and happiness. Now, she shows you exactly how to put her ideas into practice with a companion workbook that clearly guides you through the process. Designed to work hand-in-hand with Own It. Love It Make It Work ., the Workbook supplements each chapter with exercises, guidance, and tools to execute Tate's strategy seamlessly. You'll navigate through each concept based on your own situation and personal career goals. In addition to complementary material, the workbook also features entirely new content, including: • Questions to help you clarify your career goals and what you need to be engaged and fulfilled • Concepts that you and your colleagues can explore together • A revealing quiz that will show you which action step to take first, second, third, until you have your dream job • Hands-on practices to cultivate happiness and well being • How trust and purpose can become the bedrock of your professional life A practical tool kit to leverage your unique strengths, skills and talents and custom-build your career, this all-new workbook offers you a refreshing opportunity for a radical realignment of your work, your goals, and your entire life.